Lmcd1/Dyxin, a novel Z-disc associated LIM protein, mediates cardiac hypertrophy in vitro and in vivo - Frank, Derk; Frauen, Robert Christian; Hanselmann, Christiane; Kuhn, Christian; Will, Rainer D.; Gantenberg, Johanne; Füzesi, Laszlo; Katus, Hugo; Frey, Norbert (Journal of molecular and cellular cardiology, 2010)
To identify new mediators of cardiac hypertrophy, we performed a genome-wide mRNA screen of stretched neonatal rat cardiomyocytes (NRCMs). In addition to known members of the hypertrophic gene program, we found the novel sarcomeric Z-disc LIM protein Lmcd1/Dyxin markedly upregulated. Consistently, Lmcd1 was also induced in several mouse models of myocardial hypertrophy suggesting a causal role in cardiac hypertrophy. We overexpressed Lmcd1 in NRCM, which led to cardiomyocyte hypertrophy and induction of the hypertrophic gene program. Likewise, the calcineurin-responsive gene RCAN1-4 was found significantly upregulated. Conversely, knockdown of Lmcd1 blunted the response to hypertrophic stimuli such as stretch and phenylephrine (PE), suggesting that Lmcd1 is required for the hypertrophic response. Furthermore, PE-mediated activation of calcineurin was completely blocked by knockdown of Lmcd1. To confirm these results in vivo, we generated transgenic mice with cardiac-restricted overexpression of Lmcd1. Despite normal cardiac function, adult transgenic mice displayed significant cardiac hypertrophy, again accompanied by induction of hypertrophic marker genes such as ANF and α-skeletal actin. Likewise, Rcan1-4 was found upregulated. Moreover, when crossed with transgenic mice overexpressing constitutionally active calcineurin, Lmcd1 transgenic mice revealed an exacerbated cardiomyopathic phenotype with depressed contractile function and further increased cardiomyocyte hypertrophy. We show that the novel z-disc protein Lmcd1/Dyxin is significantly upregulated in several models of cardiac hypertrophy. Lmcd1/Dyxin potently induces cardiomyocyte hypertrophy both in vitro and in vivo, while knockdown of this molecule prevents hypertrophy. Mechanistically, Lmcd1/Dyxin appears to signal through the calcineurin pathway. Lmcd1/Dyxin may thus represent an attractive target for novel antihypertrophic strategies.